An evaluation of DREADD receptor pharmacology in recombinant cells and astrocytes - Carpenter, Jessica (2020)
The M1 muscarinic acetylcholine receptor (mAChR) is a G protein-coupled receptor (GPCR), linked to cellular signalling pathways via increased intracellular calcium concentrations. The M1 mAChR has been implemented in a number of physiological and pathological signalling mechanisms in the central nervous system (CNS). In addition, a significant role of Gαq-signalling has emerged in astrocytes as continuing roles for these CNS cells are discovered. As such, the M1 receptor continues to be investigated for CNS disorders, such as Alzheimer’s disease; however, there are challenges associated with evaluating the specific role of individual mAChR subtypes, and also selective pharmacological targeting of these receptors due to the conserved nature of the orthosteric acetylcholine binding sites. Many cholinergic drugs therefore have negative non-selective side effects that limit their clinical efficacy. As an alternative, muscarinic receptor allosteric modulators may offer more spatiotemporal control of CNS pathways, and the possibility of increased subtype selectivity, to modulate M1 signalling. In parallel, DREADDs (designer receptors exclusively activated by designer drugs) provide an experimental method to study subtype selective signalling of muscarinic GPCRs, because they can be selectively activated by clozapine-N-oxide (CNO) – an otherwise biologically inert compound. This thesis first explored the use of the M1-DREADD receptor as an approach to examine allosteric modulation of signalling in recombinant systems, developing novel luciferase complementation assays to monitor effector recruitment and fluorescent ligand binding approaches, in comparison to more routine calcium mobilisation assays. Single cell calcium analysis and a morphological assay of stellation assessed the role of muscarinic signalling in primary astrocyte cells, with an intention to develop the M1-DREADD system for pharmacological control of calcium signalling in these cells. Recombinant CHO and HEK293 cell lines were developed that expressed SNAP-tagged M1 wild type (WT) or M1-DREADD receptors for evaluation of calcium signalling and receptor internalisation, and the recruitment of either a mini Gq protein or -arrestin2 measured using luciferase complementation. In calcium assays, the M1-DREADD receptor demonstrated the expected orthosteric ligand pharmacology, highlighting the high potency of CNO metabolites, such as clozapine, that might be expected to be present during in vivo experiments. The representative M1 allosteric modulator benzyl quinolone carboxylic acid (BQCA) acted as a positive allosteric modulator (PAM) of the M1-DREADD receptor signalling in the presence of CNO, and other clozapine derivatives, consistent with the preservation of its allosteric binding site in this DREADD. Luciferase complementation assays detected the real time recruitment of mini Gq proteins or β-arrestin2 to the M1-DREADD and M1-WT receptors, together with the modulation of orthosteric agonist responses by BQCA. Finally, novel fluorescent pirenzepine-based tracers were identified with high affinity for the M1 DREADD receptor and these established a competition binding assay, from which the affinities of CNO and derivatives could be established. BQCA increased the affinity of these ligands in the binding assay, but also itself competed directly for the fluorescent tracer. Finally, the role of muscarinic receptor signalling in astrocytes was investigated, in terms of calcium signalling and their role in forming a stellate morphology through modulation of Gαs cAMP-led pathways. Clozapine, and its derivatives, did not produce any off-target effects at the non-transfected astrocytes highlighting their use for selective activation of the muscarinic DREADD receptors within this cell type. However, it was shown that endogenous expression of muscarinic receptors in these primary cells could be a limitation when evaluating allosteric modulation. The M1-selective modulator BQCA did not act as a PAM when evaluating astrocytic calcium signalling, induced by acetylcholine and carbachol, perhaps due to the increased expression of M3 mAChRs, compared to M1 mAChRs, reported in these cells. It was not possible to recombinantly express the DREADDs sufficiently within primary astrocytes to study their signalling. In the future, the lack of muscarinic activation of endogenous Gαs signalling pathways in astrocytes indicates that a chimeric M3-DREADD coupled to Gαs might be a potentially selective tool to explore cAMP-dependent effects on the astrocytic cytoskeleton. These data provide further insight into the signalling of the M1-DREADD receptor in response to orthosteric and allosteric ligands, and demonstrate the applicability of mini Gq and -arrestin2 luciferase complementation to monitor the kinetics of these responses. The identification of a fluorescence ligands for these receptors opens the way to new homogeneous binding assays to study their pharmacology in more depth. Providing their cellular expression is improved, the use of Gq- and Gs-coupled DREADDs remain useful future options to provide novel understanding of the function and intracellular signalling pathways of astrocytes.